Preliminary study on the formulation of syariah compliant generic sustained release gliclazide tablet using xanthan gum - Mat Zin, Nik Mohamad Lukman; Abd Mubin, Anis Syazwani; Mohd Nawi, Mohamed Sufian; Helal Uddin, A.B.M.; Kasmuri, Abdul Razak; Mandal, Uttam Kumar Umar (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Gliclazide (1-(3,3a,4,5,6,6a-hexahydro-1H-cyclopenta[c]pyrrol-2-yl)-3-(4-methylphenyl)sulfonylurea) is a second-generation sulfonylurea which is orally administered in the treatment of non-insulin-dependent diabetes mellitus in adults. Sustain release drugs help to improve drugs bioavailability by controlling the time of drug release or prolonging it. We are reporting the preliminary formulation of sustain release gliclazide tablets with careful choice of all the ingredients and processes related to syariah compliance manufacturing of pharmaceutical products. In this work, xanthan gum, a natural gum was used to achieve the sustain release criteria. The tablets were produced by wet granulation and semi-automatic tableting process. Tablet characterisation was done following the British Pharmacopoeia (BP) criteria. We expect that the outcome of our study will result in a suitable formulation that could be useful for the formulation of such product that will be helpful for the Muslim patient especially during the fasting month.